David and Goliath in sustainable fashion: strategic business alliances in the UK fashion industry. (1st January 2014) - Thopte, Ishwari; Poldner, Kim
This paper analyses the different types of strategic alliances currently present in the UK sustainable fashion industry. According to Ethical Corporation Magazine (2006), multinationals use three methods to move into the ethical sector: a) launching new ethical products; b) buying or taking over ethical brands; c) by forming strategic alliances with sustainable fashion small to medium enterprises (SMEs). This study aims to fill a void in the literature by focusing on strategic alliances and the motivations behind forming these alliances. Through a mixed method approach, we take a closer look although the small entrepreneurial 'David's' and established multinational 'Goliaths' in the UK fashion industry interact and develop new 'ethical' collections, campaigns and brands. Our theoretical model proposes significance between the following variables; age, target market and motivations of the type of alliance formed. This model is useful for managers to determine the type of alliance they need in order to fulfil their requirements from an alliance.